Application of Raw Material Inventory Control in Neko Neko Bakery and Cake With EOQ Method For Multi Item - Fahira Mirza Putri; Harahap, Agus Salim (Talenta Publisher, 2021)
Inventory control is important action in calculating the optimal amount of the inventory level that required. The raw materials’ supply is the one factors in the production process. The lack of raw materials can make the production process gonna be hung up, otherwise the excess of raw materials can make increasing in storage cost and other costs, This research is the application of the Economic Order Quantity (EOQ) method. It used Lilliefors Normality Test to found the normality of the data. From the calculations from the EOQ method in this study found that the total cost of raw material supplies according to Neko Neko Bakery & Cake was amounted to Rp. 9.699.331,24. While from EOQ was amounted to Rp. 6.713.210,99. And using this method, the company can saving their cost to Rp. 2.986.120,25 from the Total Inventory Cost Calculation.